The Relationship between Oil Prices and Exchange Rate in Russia - Blokhina, Tatiana K.; Karpenko, Oksana A.; Guirinskiy, Andrey V. (International Journal of Energy Economics and Policy, 2016)
This paper studies the relationship between oil price and the exchange rates in Russian Federation. There is a close interrelation between the currency rate of dollar to ruble and oil prices. The regression model has accurately shown this interrelation. The interrelation with a foreign policy factor - sanctions of the USA and the European Union is also revealed. There is a close interrelation between the currency rate of dollar to ruble and oil prices. The regression model has accurately shown this interrelation. Oil prices of the Brent oil is the dominating factor in a currency exchange rate formation mechanism of ruble, at least, in the long term. When world oil prices are stabilized and sanctions cancelled, currency fluctuations and uncertainty will be minimized. The findings of this paper may be used by foreign and domestic investors while taking decisions because all the shocks impact on the economy in short and long term. Keywords: oil price, exchange rate, interrelation with a foreign policy factor JEL Classifications: C58, F31, Q35